2017
DOI: 10.2337/dc16-1787
|View full text |Cite
|
Sign up to set email alerts
|

Management of Nonalcoholic Fatty Liver Disease in Patients With Type 2 Diabetes: A Call to Action

Abstract: Traditionally a disease of hepatologists, nonalcoholic fatty liver disease (NAFLD) has recently become a major concern for a broad spectrum of health care providers. Endocrinologists and those caring for patients with type 2 diabetes mellitus (T2DM) are at center stage, as T2DM appears to worsen the course of NAFLD and the liver disease makes diabetes management more challenging. However, the nature of this relationship remains incompletely understood. Although the increasing prevalence of NAFLD is frequently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
231
1
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 288 publications
(272 citation statements)
references
References 121 publications
8
231
1
16
Order By: Relevance
“…This mixed message about screening and intervention is understandable as the impact of early intervention on the natural history of steatohepatitis is incomplete. For instance, controlled trials of lifestyle interventions have all been shorter than 1‐year and few pharmacological interventions for NASH have gone beyond 2‐3 years . However, screening strategies for many diseases were originally not as evidence‐based as desired and vague guidelines risk confusing clinicians and resulting in inaction in primary care.…”
Section: Role Of the Diabetologist In The Management Of Nashmentioning
confidence: 99%
See 1 more Smart Citation
“…This mixed message about screening and intervention is understandable as the impact of early intervention on the natural history of steatohepatitis is incomplete. For instance, controlled trials of lifestyle interventions have all been shorter than 1‐year and few pharmacological interventions for NASH have gone beyond 2‐3 years . However, screening strategies for many diseases were originally not as evidence‐based as desired and vague guidelines risk confusing clinicians and resulting in inaction in primary care.…”
Section: Role Of the Diabetologist In The Management Of Nashmentioning
confidence: 99%
“…Of note, the model did not include the potentially higher rates of diabetes‐related micro‐ and macrovascular complications associated with NASH . These findings should alarm diabetologists and prompt them to become proactive by viewing NASH as a common and serious complication of T2DM that should be systematically screened …”
mentioning
confidence: 99%
“…Vitamin E has been used with some success in non-diabetic patients 3. Newer agents tested including obeticholic acid and elafibranor have shown modest improvement on liver histology in NASH, but larger trials fully examining their safety and efficacy are ongoing 5. However, glucagon-like peptide-1 receptor agonists (GLP-1 RAs) have recently emerged as an attractive treatment option for patients with obesity and NASH.…”
Section: Treatment Of Obesity and Nafldmentioning
confidence: 99%
“…One of the main target audiences of these efforts should be the physicians that follow diabetic patients. As commented by Bertot et al, recent articles have shown a high prevalence of undiagnosed advanced fibrosis and cirrhosis in diabetic patients showing that NAFLD is an important health threat to diabetic individuals (14). In spite of that, recent guidelines from the American Diabetes Association include only a short paragraph on NAFLD without any recommendations on screening, diagnostic, or therapeutic actions (15).…”
mentioning
confidence: 99%